Users' Opinions of Archival Display - Duff, Wendy (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This paper reports on a study that used focus group research to obtain the opinions of archival users on the content and presentation of descriptions in archival information systems. The research builds on and extends a previous research study on bibliographic displays (Cherry and Howarth, 1994). This study addressed two research questions: 1) What information about archival. . .